Implementasi Pendidikan Karakter melalui Budaya Sekolah di SD Amanah Kota Tangerang - Arina, Allif Via; Magdalena, Ina; Fadilah, Ahmad Arif (Lembaga Yasin AlSys, 2022)
This study aims to determine the implementation of character education through school culture at Amanah Elementary School. This research is a descriptive qualitative research, namely research that describes and analyzes data objectively according to the data found in the field, also because in this study did not use statistical analysis procedures or data processing procedures in the form of numbers. Data collection techniques in this study used interviews techniques, observation techniques, and documentation study techniques. The research subjects consisted of principals, teachers, and students. Subject selection was chosen based on certain considerations. The results showed that SD Amanah had achieved indicators of school success in implementing character education through the school culture itself. The character values implemented through school culture include: discipline, creativity, national spirit, respect for achievement, friendly/ communicative, peace-loving.